I have to prove that $\sigma = 1/(1 + \rho)$ for the CES production function:

\begin{align} q = (l^\rho + k^\rho)^\frac{1}{\rho} \end{align}

I found out that I need to solve the following equation: \begin{align} \sigma = \frac{\frac{d(k/l)}{k/l}}{\frac{dRTS}{RTS}} = \frac{d(k/l)}{dRTS}\frac{RTS}{k/l} = \frac{d(k/l)}{d((k/l)^{1-\rho})}\frac{(k/l)^{1-\rho}}{k/l} \end{align}

But i just don't know how to rewrite this expression to $\sigma = 1/(1 + \rho)$


2 Answers 2


The production function is: $$q = (l^\rho + k^\rho)^\frac{1}{\rho}$$ The MPL and MPK are respectively: $$q_l = \frac{\partial q}{\partial l} = \frac{1}{\rho} \cdot (l^\rho + k^\rho)^{\frac{1}{\rho}-1} \cdot \rho\cdot l^{\rho-1}$$ $$q_k = \frac{\partial q}{\partial k} = \frac{1}{\rho} \cdot (l^\rho + k^\rho)^{\frac{1}{\rho}-1} \cdot \rho\cdot k^{\rho-1}$$ What is the rate that l can be substituted for k?

Where $f$ is a differentiable real-valued function of a single variable, we define the elasticity of f(x) with respect to x (at the point x) to be $$\sigma(x) = \frac{x f'(x)}{f(x)}\equiv \frac{\frac{df(x)}{f(x)}}{\frac{dx}{x}}$$

  1. Do a change of variables such that $u = ln(x)$ ($\rightarrow x = e^u$) and $v=ln(f(x))$ ($\rightarrow f(x) = e^v$)
  2. Note that $v' = f'(x) / f(x)$ and $u'=\frac{1}{x}$ so that $$\frac{v'}{u'}=\frac{\frac{f'(x)}{f(x)}}{\frac{1}{x}} = \sigma(x)$$
  3. Note that this is also the result you get by solving for $ \frac{d ln f(x)}{d ln(x)}$ because $ \frac{d ln f(x)}{d ln(x)} = \frac{d v}{d u}$ which we solve via the chain rule: $$ \frac{d v}{d u} = \frac{d v}{d x} \cdot \frac{d x}{d u} = \frac{f'(x)}{f(x)} \cdot x $$ which happens to be exactly the definition of $\sigma(x)$.

Now let's tackle your elasticity problem.

$$ ln(\frac{q_k}{q_l})= log(\frac{\frac{1}{\rho} \cdot (l^\rho + k^\rho)^{\frac{1}{\rho}-1} \cdot \rho\cdot l^{\rho-1}}{\frac{1}{\rho} \cdot (l^\rho + k^\rho)^{\frac{1}{\rho}-1} \cdot \rho\cdot k^{\rho-1}}) = ln (\frac{l}{k})^{\rho-1} = (\rho-1) ln (l/k) = (1 - \rho) ln (k/l)$$ $$ \Rightarrow ln (k/l) = \frac{1}{1-\rho} \cdot ln(\frac{q_k}{q_l})$$

So $\sigma = \frac{1}{1-\rho}$

  • $\begingroup$ $\frac{1}{\rho}$ and $\rho$ can be reduced from derivatives MPL and MPK to simplify the exposition. $\endgroup$
    – garej
    May 11, 2018 at 15:28

I would like to add a little bit to the answer above. I wrote a comment earlier, but I thought it'd be helpful to flesh out the argument a little more.

We have a firm that uses two factors of production, labor $l$ and capital $k$, to produce output. Quantity of output is written $q$.

The elasticity of a function of a single variable measures the percentage response of a dependent variable to a percentage change in the independent variable.

On the other hand, the elasticity of substitution between two factor inputs measures the percentage response of the ratio of their quantities to a percentage change in the relative marginal products.

Pertaining to the above, we have that the elasticity is given by

\begin{align} \sigma \equiv \frac{d \ln{\left( k/l \right)}}{d\ln{ \left( MPL/MPK \right)}} \end{align}

where $MPL$ is the marginal product of labor and $MPK$ is the marginal product of capital.

The reason I am writing this out is that there is a small error in the above answer. In the equation right after "Now let's tackle your elasticity problem," $\ln{\frac{q_k}{q_l}}$ is immediately followed by an expression for $\ln{\frac{q_l}{q_k}}$ switching the numerator with the denominator.

If you correct this, you get that $\sigma = -\frac{1}{1-\rho}$, which is close but not quite correct. To get the correct answer, you follow otherwise exactly the same calculations given by the above answer to get

$$ \ln{k/l} = \frac{1}{1-\rho}\cdot \ln {\frac{q_l}{q_k}}$$

to get that $\sigma = \frac{1}{1-\rho}$, where the corrections are for reasons outlined above.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.